Nigella sativa extract improves seminiferous tubule epithelial thickness in lead acetate-exposed balb/c mice - Diana, Alis Nur; I'tishom, Reny; Sudjarwo, Sri Agus (Folia Medica Indonesiana, 2017)
Lead that enters the body may lead to increased production of ROS (Reactive Oxygen Species) that may affect reproductive system. Black cumin (Nigella sativa) extract contains high antioxidant, tymoquinone, that may be used to suppress oxidative stress induced by lead in animal experiments. This study aimed to prove that black cumin (Nigella sativa) extract improves the thickness of seminiferous tubular epithelium in Balb/c mice exposed to lead (Pb) acetate. This study used post-test only control group design. The subjects in this study were 30 Balb/c male mice (Mus musculus), divided into 5 groups. K-group: control group without lead acetate and black cumin extract, K+ group: group with 50 mg/kgBW of lead acetate for 28 days, P1 group: treatment group with 50 mg/kgBW of lead acetate for 28 days + 0.3 mg/gBW of black cumin extract for 21 days, P2 group: treatment group with 50 mg/kgBW of lead acetate for 28 days + 0.6 mg/gBW of black cumin extract for 21 days, and P3 group: treatment group with 50 mg/gBW of lead acetate for 28 days + 1.2 mg/gBW black cumin extract for 21 days. The results showed that the mean ± standard deviation of the highest thickness of seminiferous tubular epithelium was 45.80 ± 2.73 in the group that was exposed to acetate + 0.6 mg/gBW of black cumin (P2), and the lowest was 32.75 ± 4.07 in the group that was exposed to lead acetate (K+). The results were then analyzed by Anova test. The results showed that there was significant differences in the thickness of seminiferous tubular epithelium between P1, P2, P3 and K+. In conclusion, black cumin extract administration was proved to improve the thickness of seminiferous tubular epithelium in lead (Pb) acetate-exposed Balb/c mice (Mus musculus).